Glycoinositolphospholipid from Trypanosoma cruzi: structure, biosynthesis and immunobiology. - Previato, J; Wait, R; Jones, C; DosReis, G; Todeschini, A; Heise, N; Previato, L (2004)
The pathogenic protozoan parasite Trypanosoma cruzi expresses on its surface an unusual family of glycoinositolphospholipids (GIPLs) closely related to glycosylphosphatidylinositol (GPI) anchors. Different parasite isolates express distinct GIPLs which fall into two series, depending on the substitution of the third mannosyl residue in the conserved glycan sequence Man4-(AEP)-GlcN-InsPO4 by ethanolamine phosphate or beta-galactofuranose. Although the exact role of these molecules in the cell biology and pathogenicity of T. cruzi remains unknown, the lipid and glycan moieties impart distinct responses to host T and B lymphocytes and phagocytes, overall favouring an immune response permissive to the parasite. The biosynsthesis of GIPLs follows a pathway similar to that observed for GPI anchors. However, a more detailed understanding might enable the development of specific inhibitors of parasite-specific enzymes and lead to novel drugs to ameliorate Chagas disease.